2009
DOI: 10.1007/s12282-009-0148-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of high-dose toremifene in patients relapsed on treatment with an aromatase inhibitor

Abstract: TOR120 was rated excellent in acceptability, and high efficacy was observed when it was used up to third-line treatment for AI-failure cases, although this study may show some selection bias because of the retrospective study. In addition, it was also considered effective for TAM-failure cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
0
13
1
Order By: Relevance
“…Several studies showed that constitutively active ESR1 ligand-binding domain mutations in pretreated advanced ER-positive breast cancers confer partial resistance to antiestrogens such as tamoxifen and fulvestrant, and higher doses of these drugs could inhibit mutant ERα tumors [18][19][20]. Yamamoto and colleagues demonstrated that high-dose toremifene (120 mg daily) was effective in patients with metastatic breast cancer who showed progression of the disease during aromatase inhibitors therapy, although the mechanisms of action of high-dose toremifene have not fully been understood [14,21]. It is suggested that high-dose SERMs and fulvestrant 500 mg might be effective in tumors with constitutively active ESR1 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that constitutively active ESR1 ligand-binding domain mutations in pretreated advanced ER-positive breast cancers confer partial resistance to antiestrogens such as tamoxifen and fulvestrant, and higher doses of these drugs could inhibit mutant ERα tumors [18][19][20]. Yamamoto and colleagues demonstrated that high-dose toremifene (120 mg daily) was effective in patients with metastatic breast cancer who showed progression of the disease during aromatase inhibitors therapy, although the mechanisms of action of high-dose toremifene have not fully been understood [14,21]. It is suggested that high-dose SERMs and fulvestrant 500 mg might be effective in tumors with constitutively active ESR1 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In a larger retrospective study in which the efficacy of 120 mg TOR was analyzed with AI-failure cases (n=80), ORR and CB were 15 and 45%, respectively (19). In cases where tamoxifen preceded AI, high-dose TOR was effective for tamoxifenresistant breast cancer (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…The OR was 4.2 -10.0% and the clinical benefit rate was 20.0 -40.0%. Regarding TOR, a high dose TOR showed OR of 15% and CB rate of 45.0% in a retrospective study 12) , and it is suggested that high 13) . And high dose TOR has shown efficacy in patients who progressed on TAM 14,15) .…”
Section: Discussionmentioning
confidence: 95%